Analisis Kinerja Perusahaan Menggunakan Metode Performance Prism pada PT John Wise Sejahtera: Analysis of Company Performance Using the Performance Prism Method at PT John Wise Sejahtera - Olosius, Ave; Masahere, Usran (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the performance of PT John Wise Sejahtera using the Performance Prism approach, which consists of five dimensions: stakeholder satisfaction, stakeholder contribution, strategies, processes, and capabilities. The research employed a non-statistical quantitative method, with data collected through questionnaires distributed to employees as research respondents. The collected data were analyzed descriptively using frequency distributions, percentages, and mean scores to describe the company’s performance condition objectively. The results indicate that the overall performance of PT John Wise Sejahtera is categorized as good to very good. Employees show a positive level of satisfaction with the working environment and work system, as well as a high level of contribution and loyalty toward the company. The company’s strategies are considered clear and relevant in supporting the quality of logistics services. Operational processes have been implemented in accordance with standard operating procedures and support timely delivery, while the company’s capabilities are deemed adequate in responding to challenges within the logistics industry. This study demonstrates that the Performance Prism approach provides a comprehensive and integrated overview of organizational performance